Continuous Moderate-Intensity but Not High-Intensity Interval Training Improves Immune Function Biomarkers in Healthy Young Men. Issue 1 (January 2020) - Khammassi, Marwa; Ouerghi, Nejmeddine; Said, Mohamed; Feki, Moncef; Khammassi, Yosra; Pereira, Bruno; Thivel, David; Bouassida, Anissa
Abstract : Abstract: Khammassi, M, Ouerghi, N, Said, M, Feki, M, Khammassi, Y, Pereira, B, Thivel, D, and Bouassida, A. Continuous moderate-intensity but not high-intensity interval training improves immune function biomarkers in healthy young men. J Strength Cond Res 34(1): 249–256, 2020—Effects of endurance running methods on hematological profile are still poorly known. This study aimed to compare the effects of 2 training regimes; high-intensity interval training (HIIT) and moderate-intensity continuous training (MCT) performed at the same external load on hematological biomarkers in active young men. Sixteen men aged 18–20 years were randomly assigned to HIIT or MCT group. Aerobic capacity and hematological biomarkers were assessed before and after 9 weeks of interventions. At baseline, aerobic and hematological parameters were similar for the 2 groups. After intervention, no significant change was observed in maximal aerobic velocity and estimated VO2 max in both groups. Leukocyte ( p < 0.01), lymphocyte ( p < 0.05), neutrophil ( p < 0.05), and monocyte ( p < 0.01) count showed significant improvements in response to the MCT compared with the HIIT intervention. The MCT intervention favored an increase in the number of immune cells, whereas the opposite occurred as a result of the HIIT intervention. These findings suggest that MCT interventions might be superior to HIIT regimes in improving immune function in active young men.